1999
DOI: 10.1111/j.1574-695x.1999.tb01320.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of infection in sudden infant death syndrome

Abstract: Studies on the potential role of infectious agents in sudden infant death syndrome (SIDS) have been published over the years in a variety of journals. The aim of this special issue of FEMS Immunology and Medical Microbiology is to bring together a group of the most recent studies from Europe, Australia and Canada which cover epidemiology and laboratory studies examining hypotheses relating to infection and inflammation in SIDS. The articles in this issue examine evidence for the involvement of specific micro-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Prone sleeping and exposure to cigarette smoke are important factors favoring the development of SIDS. 1,12 Recently, Krous et al 12 even reported that in their group of SIDS infants, both the percentage of positive upper respiratory tract cultures (80% vs. 89%, respectively) and pathologic inflammatory lymphocytic infiltrations of the bronchi, bronchioles, and pulmonary interstitium were similar to those found in controls. 6 Several authors believe that SIDS is a pathophysiologic reaction to bacterial toxins, viruses, and/or cigarette smoke effects during the early stage of developmental age when defense reactions of the organism are less effective in neutralizing inflammatory mediator effects.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Prone sleeping and exposure to cigarette smoke are important factors favoring the development of SIDS. 1,12 Recently, Krous et al 12 even reported that in their group of SIDS infants, both the percentage of positive upper respiratory tract cultures (80% vs. 89%, respectively) and pathologic inflammatory lymphocytic infiltrations of the bronchi, bronchioles, and pulmonary interstitium were similar to those found in controls. 6 Several authors believe that SIDS is a pathophysiologic reaction to bacterial toxins, viruses, and/or cigarette smoke effects during the early stage of developmental age when defense reactions of the organism are less effective in neutralizing inflammatory mediator effects.…”
Section: Introductionmentioning
confidence: 83%
“…1 Accounting for 2529 deaths in 1998 in the United States, SIDS is the third leading cause of infant mortality (8.9%) after congenital anomalies (22%) and short gestation/low birth weight (14%). 1 Accounting for 2529 deaths in 1998 in the United States, SIDS is the third leading cause of infant mortality (8.9%) after congenital anomalies (22%) and short gestation/low birth weight (14%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many SIDS infants have a history of a mild viral illness that precedes death but is not thought to be its cause (2, 11, 12). Increased incidence of SIDS in winter months parallels closely a susceptibility to infections, particularly those of the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…A p value less than 0.05 was considered significant. Positive cultures were specifically classified according to whether ‘group 2 pathogens’ were present, these being organisms that may be clinically associated with bacteraemic septic shock in the absence of an identifiable focus of infection, as previously defined 6 9…”
Section: Methodsmentioning
confidence: 99%